Pengaruh Profitabilitas dan Likuiditas Terhadap Harga Saham Dengan Earning per Share (EPS) Sebagai Varibel Moderating Pada PT Astra Internasional, Tbk Periode Tahun 2016-2023 - Laili, Ida Asmaul; Idris, Ahmad; Afrianto, Dadang (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
The influence of profitability here uses two ratio indicators: Return on Assets (ROA) and Return on Equity (ROE). Meanwhile, the researcher used two ratio indicators to influence liquidity: the Current Ratio (CR) and the Quick Ratio (QR). This study also used a moderating variable, Earnings Per Share (EPS). The research took place at PT Astra International, Tbk. Astra is one of the largest public companies in Indonesia with over 200 subsidiaries, joint ventures, and associated entities, and over 200,000 employees. The company's diversified business model creates synergies and opportunities across all industry sectors, including: Automotive. Astra's automotive business includes four-wheeled vehicles, two-wheeled vehicles, components, and other automotive-related products and services, as well as financial services. The sampling technique used in this study was purposive sampling. Based on the criteria used, the sample in this study is the quarterly financial report of PT Astra Internasional, Tbk for the period 2016 - 2023 or for 8 years totaling 32 samples which include data on financial ratios using profitability ratios with 2 ratio indicators, namely: Return On Assets (ROA), Return On Equity (ROE). As well as liquidity ratios with 2 indicators, namely: Current Ratio (CR), Quick Ratio (Quick Ratio) using Earning Per Share (EPS) as a Moderating variable on Stock Prices. From the results of this study, it can be concluded that the results of the analysis show that only Liquidity (X2) has a negative and statistically significant effect with a medium effect size on Y. Meanwhile, Profitability (X1) and Z do not have a significant direct effect, and the moderating effect of Z is also insignificant. This model has limited explanatory power for variable Y.